Clinical and 3-Dimensional Radiographic Evaluation of Autogenous Iliac Block Bone Grafting and Guided Bone Regeneration in Patients With Atrophic Maxilla - BORAHAN, MEHMET OĞUZ (W B SAUNDERS CO-ELSEVIER INC, 2017)
Purpose: To evaluate the rate of graft resorption in autogenous iliac bone grafting (IBG) and guided bone regeneration (GBR) in patients with atrophic maxillae. Materials and Methods: We performed a retrospective study involving patients requiring implant placement who underwent IBG or GBR. Volumetric changes of the graft sites were evaluated by imaging studies. The primary predictor and outcome variables were augmentation technique and rate of volumetric resorption, respectively. Secondary outcome variables included bone gain, success of grafting, insertion torque of implants, and requirement for vestibuloplasty. Results: The sample comprised 39 patients (21 with GBR and 18 with IBG). One patient in the IBG group had temporary sensory disturbance at the donor site, and one patient in the GBR group had late exposure of the nonresorbable membrane. The average values of percent volume reduction in the GBR and IBG groups were 12.26% +/- 2.35% and 35.94% +/- 7.94%, respectively, after healing and 15.87% +/- 1.99% and 41.62% +/- 6.97%, respectively, at last follow-up. The IBG group exhibited a significantly higher reduction in bone volume than the GBR group at both time points (P =.001). The mean values of horizontal and vertical bone gain after healing in the IBG group were significantly higher than those in the GBR group (P = .006 and P = .001, respectively). The mean implant torque during implant placement in the GBR group was significantly higher than that in the IBG group (P = .024). There was no significant difference in the requirement for vestibuloplasty between the two groups (P >.05). Conclusions: Although both hard tissue augmentation approaches provide an adequate volume of bone graft for implant insertion, IBG results in greater graft resorption at maxillary augmented sites than GBR. Clinicians should consider the differences in the extent of graft resorption between the two methods while choosing the treatment approach. (C) 2016 American Association of Oral and Maxillofacial Surgeons
Keywords: ALVEOLAR RIDGE AUGMENTATION; PROSPECTIVE CASE SERIES; CREST ONLAY GRAFTS; ENDOSSEOUS IMPLANTS; BOVINE BONE; FOLLOW-UP; ENDOSTEAL IMPLANTS; RECONSTRUCTION; PLACEMENT; VOLUME